Parenteral adjuvant effects of an enterotoxigenic Escherichia coli (ETEC) natural heat-labile toxin variant - Catarina Joelma Magalhães Braga; Catarina Joelma Magalhães Braga; Juliana Falcão Rodrigues; Yordanka eMedina-Armenteros; Luis Ernesto Farinha-Arcieri; Armando Morais Ventura; Silvia Beatriz Boscardin; Maria Elisabete Sbrogio-Almeida; Luis Carlos de Souza Ferreira (Frontiers in Immunology, 2014)
Native type I heat-labile toxins (LTs) produced by enterotoxigenic Escherichia coli (ETEC) strains exert strong adjuvant effects on both antibody and T cell responses to soluble and particulate antigens following co-administration via mucosal routes. However, inherent enterotoxicity and neurotoxicity (following intranasal delivery) had reduced the interest in the use of these toxins as mucosal adjuvants. LTs can also behave as powerful and safe adjuvants following delivery via parenteral routes, particularly for activation of cytotoxic lymphocytes. In the present study, we evaluated the adjuvant effects of a new natural LT polymorphic form (LT2), after delivery via intradermal (i.d.) and subcutaneous (s.c.) routes, with regard to both antibody and T cell responses. A recombinant HIV-1 p24 protein was employed as a model antigen for determination of antigen-specific immune responses while the reference LT (LT1), produced by the ETEC H10407 strain, and a non-toxigenic LT form (LTK63) were employed as previously characterized LT types. LT-treated mice submitted to a four dose-base immunization regimen elicited similar p24-specific serum IgG responses and CD4+ T cell activation. Nonetheless, mice immunised with LT1 or LT2 induced higher numbers of antigen-specific CD8+ T cells and in vivo cytotoxic responses compared to mice immunised with the non-toxic LT derivative. These effects were correlated with stronger activation of local dendritic cell populations. In addition, mice immunized with LT1 and LT2, but not with LTK63, via s.c. or i.d. routes developed local inflammatory reactions. Altogether, the present results confirmed that the two most prevalent natural polymorphic LT variants (LT1 or LT2) display similar and strong adjuvant effects for subunit vaccines administered via i.d. or s.c. routes.